The Clinical, Radiological, and Electrophysiological Profile of Children Presenting with Acute Fulminant Cerebral Edema Due to Suspected Encephalitis in an Eastern Indian Tertiary Care Center - Das, Suman; Ray, Biman Kanti; Mondal, Gobinda; Paul, Dilip Kumar; Chatterjee, Kaushani; Mishra, Lopamudra (Journal of Pediatric Neurology, 2022)
Objective Our objective was to describe the clinicodemographic, laboratory, and outcome profiles of a rare phenotype of pediatric acute encephalitis syndrome (AES) with acute fulminant cerebral edema (AFCE) and compare them with that of AES without AFCE.Methods We retrospectively analyzed medical records of a cluster of children hospitalized with encephalitis between June 1, 2021 and December 31, 2021. Their clinical and demographic features, laboratory investigations (hematological, biochemical, serological, microbiological, radiological, and electrophysiological tests), and follow-up data up to 3 months postdischarge were recorded. Patients with AFCE and those without it were divided into groups A and B, respectively, and their characteristics were compared.Results There were 11 and 15 patients in groups A and B, respectively. There were no significant differences between the two groups in terms of sex, neurological status at admission, hematological and cerebrospinal fluid values, pediatric intensive care unit (PICU) course, and management, etiological identification, and mortality and disabilities at discharge. Patients having reversal or having white cerebellar signs did not significantly differ in their outcomes. However, the patients in group A had significantly lower age, higher incidence of abnormal findings on head computed tomography scans at admission, longer duration of hospitalization, and neurological sequelae at 3 months. The numbers of patients with identified etiologies were zero in group A but five in group B (two Japanese encephalitis, two scrub typhus, and one dengue). Patients of group A had bilateral asymmetric temporal-parieto-occipital T2 hyperintense lesions in magnetic resonance imaging, whereas patients of group B had bifrontal predominant or thalamo-mesencephalic lesions. Multifocal epileptiform discharges were seen in electroencephalogram in both groups, which reverted to normal in 9 and 46% in groups A and B at 3 months, respectively.Conclusion Younger age is a significant risk factor for the development of AFCE in pediatric AES. AFCE patients have worse outcomes at 3 months, although they do not significantly differ from their non-AFCE counterparts at discharge. When occurring in clusters, AFCE patients exhibit the same radiological and electroencephalographic features.
Keywords: encephalitis; acute fulminant cerebral edema; reversal sign; white cerebellar sign; computed tomography